APPLICATION OF BIOSURFACTANT AND CINNAMON ESSENTIAL OIL-BASED NANOEMULSION AS ANTI-BIOFILM AGENTS AGAINST CANDIDA ALBICANS ON TEETH - Wahyuni, Nurul
Dental and oral care products commonly used to prevent biofilm formation on teeth often contain Sodium Lauryl Sulfate (SLS), which can cause allergic reactions and oral mucosa infections. Biosurfactants (BS) and cinnamon essential oil (CEO) can be safer alternatives because both are natural substances with low toxicity and antimicrobial properties. Combining these as nanoemulsion can enhance their effectiveness as antimicrobials and improve product efficiency. This research aimed to characterize and identify biosurfactant-producing bacteria, screen biosurfactants and cinnamon essential oil for inhibiting Candida albicans, produce and characterize nanoemulsions, and evaluate its antibiofilm capabilities against C. albicans. This study utilized five bacterial isolates known for their biosurfactant production. These isolates were characterized based on macroscopic and microscopic characteristics and identified using 16S rRNA marker genes. Minimum Inhibitory Concentration (MIC) tests were conducted to select cinnamon essential oil concentrations and bacterial species producing biosurfactants that effectively inhibit C. albicans growth. The selected biosurfactants were further characterized using FTIR, LC-MS, IF) analysis, and toxicity test with BLST test. Nanoemulsions were prepared using low-energy (NEL) and high-energy (NEH) methods with biosurfactant concentrations of 100 ppm, 50 ppm, 25 ppm, and 12,5 ppm mixed with 5600 ppm cinnamon essential oil. Nanoemulsions were characterized by Particle Size Analysis (PSA), Zeta potential measurement, and stability tests including freeze-thaw, centrifugation, and incubation at different temperatures (4°C, 25°C, and 37°C) over 30 days. Lastly, Minimum Biofilm Inhibitory Concentration (MBIC) and Minimum Biofilm Eradication Concentration (MBEC) tests were performed to evaluate the nanoemulsions' ability to inhibit biofilm formation and eradicate existing biofilms. Based on screening results, Bacillus altitudinis biosurfactant was identified as the most effective inhibitor of C. albicans growth with a minimum concentration of 312,5 ppm (P>0,05). The minimum inhibitory concentration of cinnamon essential oil against C. albicans growth was found to be 220 ppm. The particle sizes of NEH formulations ranged from 213 nm - 232 nm, while NEL sizes ranged from 405 nm - 567 nm with both Zeta potential ?-30 mV (P>0,05). After 24 hours, phase separation occurred in NEL nanoemulsions, whereas NEH did not experience phase separation even up to day 30 except under freeze-thaw treatment and incubation at 37°C. The minimum concentrations of NEH and NEL nanoemulsions required to inhibit biofilm formation were determined to be 25 ppm BS + 5600 ppm CEO (P<0,05), achieving inhibition percentages of 30% for NEH and 10% for NEL. For biofilm eradication, the minimum concentrations of NEH and NEL nanoemulsions were 12,5 ppm BS + 5600 ppm CEO (P>0,05), with eradication percentages of 20% for NEH and 12% for NEL. In conclusion, NEH nanoemulsions demonstrated greater stability compared to NEL nanoemulsions and exhibited higher percentages in inhibiting growth, formation, and eradication of C. albicans biofilms.